Transformation of the ionic liquid [EMIM][B(CN)4] into anionic and neutral lanthanum tetracyanoborate coordination polymers by ionothermal reactions. Issue 37 (26th April 2017) - Zottnick, Sven H.; Finze, Maik; Müller-Buschbaum, Klaus
Abstract : In ionothermal reactions, a room temperature borate-ionic liquid is directly transformed into coordination polymers by coordination to lanthanide cations. Abstract : The lanthanum tetracyanoborate coordination polymers [EMIM] 1∞[LaNO3 {B(CN)4 }3 (H2 O)3 ] (EMIM = 1-ethyl-3-methylimidazolium) and 1∞[La(NO3 )2 [B(CN)4 ](H2 O)4 ] mark first examples of Ln-tetracyanoborates that have been obtained in ionothermal syntheses without further solvents to influence e.g. viscosity. Thereby, the ionic liquid [EMIM][B(CN)4 ] is fully incorporated into product formation.